2014
DOI: 10.3390/nu6062376
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Extra Virgin Olive Oil and Soybean on DNA, Cytogenicity and Some Antioxidant Enzymes in Rats

Abstract: We investigated the effect of extra virgin (EV) olive oil and genetically modified (GM) soybean on DNA, cytogenicity and some antioxidant enzymes in rodents. Forty adult male albino rats were used in this study and divided into four groups. The control group of rodents was fed basal ration only. The second group was given basal ration mixed with EV olive oil (30%). The third group was fed basal ration mixed with GM (15%), and the fourth group survived on a combination of EV olive oil, GM and the basal ration f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 34 publications
2
5
0
1
Order By: Relevance
“…In our study, the supplementation with unsaturated fatty acids proved to be effective at improving the oxidative state of obese mice; 2-OHOA supplementation reduced both GSSG levels and the GSSG/GSH ratio, as well as MDA levels (the marker of lipid peroxidation), when compared with the OD group, while XO activity was decreased by n-3 PUFA supplementation (in relation to the OD group). Our results are in agreement with previous evidence showing that olive oil consumption can favour tissue antioxidant defence mediated by the glutathione system (De La Cruz et al 2000), reduce lipid peroxidation levels (El-Kholy et al 2014) and improve plasma antioxidant capacity (Pitsavos et al 2005). In our study, obese animals also presented higher chemotaxis, lower cytotoxic activity and lower mitogeninduced proliferation in splenic leucocytes.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In our study, the supplementation with unsaturated fatty acids proved to be effective at improving the oxidative state of obese mice; 2-OHOA supplementation reduced both GSSG levels and the GSSG/GSH ratio, as well as MDA levels (the marker of lipid peroxidation), when compared with the OD group, while XO activity was decreased by n-3 PUFA supplementation (in relation to the OD group). Our results are in agreement with previous evidence showing that olive oil consumption can favour tissue antioxidant defence mediated by the glutathione system (De La Cruz et al 2000), reduce lipid peroxidation levels (El-Kholy et al 2014) and improve plasma antioxidant capacity (Pitsavos et al 2005). In our study, obese animals also presented higher chemotaxis, lower cytotoxic activity and lower mitogeninduced proliferation in splenic leucocytes.…”
Section: Discussionsupporting
confidence: 94%
“…), reduce lipid peroxidation levels (El‐Kholy et al . ) and improve plasma antioxidant capacity (Pitsavos et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…El‐Kholy et al . () investigated the effect of extra virgin olive oil and GM soya bean in rodents. However, the study aimed to compare only olive and soya bean, instead of GM and non‐GM soya bean, so no conclusions are possible.…”
Section: Scientific Quality Of the Studiesmentioning
confidence: 99%
“…However, most of the conducted studies in human and animals confirmed the olive oil role in protecting against NAFLD, decreasing blood triglycerides, increasing high-density lipoprotein, reducing insulin resistance and hepatic steatosis [47][48][49][50][51]. It has showed that consumption of diets that rich in olive oil has a profound effect on different health outcomes, specially obesity, T2DM and metabolic syndrome [52].…”
Section: Journal Of Clinical Nutrition and Dietetics Issn 2472-1921mentioning
confidence: 99%